1098 Cardiac Output Measurements in Preterm Neonates Requiring Resuscitation at Birth. (October 2012) - Ahmed, N; Sundaram, V; Kumar, P
Abstract : Background: The effect of perinatal asphyxia on cardiac output and flow patterns in asphyxiated preterm neonates is less well understood. Objectives: To study the cardiac outputs (left and right ventricle – LVO and RVO) and superior vena cava (SVC) blood flow patterns in asphyxiated preterm neonates in first 24 hours of age. Subject and interventions: Serial echocardiography was done in preterm neonates < 34 weeks who required resuscitation, at 6±2, 12±2 and 24±4 hours using color Doppler (Sonosite). LVO, RVO and SVC flow velocity were calculated . Results: Functional Echo was done in 68 neonates with mean gestation and weight of 31±1.6 weeks and 1343± 361g. Median SVC flow, LVO and RVO at 6, 12 and 24 hrs of age were 109 (70–137), 103 (85–150) and 132 (92–181); 381 (287–493), 421 (337–510) and 408 (324–557); 327 (214–435), 328 (259–467) and 381 (280–501) ml/kg/min respectively. The differences in these three measures between three time points were not statistically significant. A statistically significant increase was seen between SVC flows at 6 versus 24 hours. No difference was observed in these measurements in 21% vs 100% oxygen groups. Conclusions: LVO, RVO and SVC flow showed an increasing trend from 6 hrs of age to 24 hrs of age. A significant increase was observed in the SVC flow between 6 and 24 hours of age suggestive of hypoperfusion-reperfusion phenomena. Resuscitating with 21% or 100 % oxygen did not show any difference in these measurements.